Chemical composition and antioxidant activity of essential oil of leaves and flowers of Alternanthera sessilis red from Sabah - Mohammad Shaheen Khan, Samina Khan Yusufzai, Lim Phaik Kaun, Muhammad Dawood Shah, Rubia Idris (Journal of Applied Pharmaceutical Science, 2016)
In the present study, chemical composition and antioxidant activity of essential oil from the aerial parts of Alternanthera sessilis red has been investigated. The chemical composition of essential oil of A. sessilis red was determined by GC-MS analysis. Determination of antioxidant nature of A. sessilis red was carried out by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method using butylated hydroxytoulene (BHT)as the positive control. The major components of essential oil of leaves, as analyzed by the GC-MS were found to be 1,1,1,5,5,5-hexamethyl-3,3-bis[trimethylsilyl)oxy]trisiloxane (15.43%), S,S-dioxide trans-2-methyl-4-N-pentylthiane (11.27%), didodecylphthalate (10.62%) and tetrahydro-2,5-dimethoxy furan (10.01%).However, the major components of essential oil of flower were 1,1,1,5,5,5-hexamethyl-3,3-bis[trimethylsilyl)oxy]trisiloxane (17.76%), trans-4-ethyl-5-octyl-2,2-bis(trifluromethyl)-1,3-dioxolane (11.12%) and tetrahydro-2,5-dimethoxy furan ( 9.10%).
Keywords: Alternanthera sessilis,Antioxidant Activity,BHT,1,1-Diphenyl-2-picrylhydrazyl,Essential Oil,GC-MS analysis.